A missiology of the road early perspectives in David Bosch's theology of mission and evangelism - Livingston, John Kevin (Cambridge : James Clarke & Co ; Eugene, Oregon : Pickwick Publications, 2013)
David Bosch (1929-1992) was one of the foremost mission theologians of the twentieth century; a prolific scholar, committed church leader and active participant in the global conciliar and evangelical mission movements. His distinctive role in the South African church's struggle against apartheid is less well known, however.After reviewing Bosch's background and exploring key themes in his understanding of mission and evangelism, Livingston explores Bosch's legacy from the perspective of the missionary nature of the church. The church is God's kingdom community, acting as a witness to and inst.
pt. 1. David Bosch in context. Apartheid and Afrikaner identity -- Bosch's theological pilgrimage: a biographical sketch -- pt. 2. Bosch's theology of mission and evangelism. Theology, mission, and missiology: Bosch's theological method -- The historical and theological context of mission: major motifs in Bosch's thought -- The biblical foundation for mission -- Mission, evangelism, and church growth -- pt. 3. Crucial theological dimensions for a missionary church. Introduction: The missionary nature of the church as the theological horizon for Bosch's missiology -- The eschatological dimension of the missionary church: the church as witness to the kingdom of God -- The ecclesial dimension of the missionary church: the church as God's "alternative community" -- The soteriological dimension of the missionary church: the church as a sign and agent of God's reconciliation -- Epilogue.
Revision of the author's thesis (Ph. D.)--University of Aberdeen, 1989 under title A missiology of the road : the theology of mission and evangelism in the writings of David J. Bosch.
Includes bibliographical references.
Description based upon print version of record. Print version is xvi, 402 pages.
Master record variable field(s) change: 072
Keywords: Bosch, David J., -- 1929-1992.; Bosch, David J., -- 1929-1992; Evangelistic work -- Philosophy; Missions -- Theory -- History -- 20th century; Missions -- Theory; South Africa -- Church history; Bosch, David Jacobus; Evangelistic work -- Philosophy; Missions -- Theory -- History -- 20th century; Missions -- Theory; South Africa -- Church history; RELIGION / Christian Ministry / Missions; Evangelistic work -- Philosophy; Missions -- Theory; South Africa; 1900 - 1999; Church history; History; Electronic books